Cross–language transfer of phonological and morphological awareness among young Malay second language learners / Anne Benedict Nair - Nair, Anne Benedict (2013)
This study seeks to investigate cross-language transfer of phonological and morphological awareness among young Malay learners who are learning English as their second language and have Malay as their L1. The study examines the relationship between phonological and morphological awareness tasks and performance on English and Malay spelling tests. The data consists of responses to 4 spelling tests and 11 awareness tasks. The data for the study was drawn from a sample of Malay learners aged seven to nine from three Malaysian urban schools. Two types of studies were undertaken, a quantitative study and a qualitative study. The quantitative study investigated if phonological awareness and morphological awareness in both Malay and English can predict English Spelling Accuracy. The qualitative study analysed phoneme and morpheme errors to determine if there was an association between Malay and English phonological and morphological awareness and an English and Malay morpheme subtest as well as a phoneme subtest. Correlations, partial correlations and regression analyses were used to analyse the data in the study. The findings suggest that there is cross-language transfer from the L1 to the L2. Regression analysis showed that Malay phonological awareness predicted English spelling accuracy in both Year 1 and Year 2 children. Malay morphological awareness predicted English spelling accuracy among Year 1 children. In the qualitative analysis it was found that there was a significant within language relationship between Malay phonological awareness and Malay phonological spelling. Malay phonological awareness was also associated with English phonological spelling. There was also a iii significant cross-language relationship between Malay morphological awareness and lenient consistency of English roots. It was also found in the qualitative study that Malay spelling of morphemes was significantly associated with English spelling of morphemes. iv